Waste utilization of sewage sludge and red mud based on chemical looping catalytic oxidation. (15th January 2023) - Song, Chen; Li, Caifu; Zhu, Dan; Chen, Wenbin; Ai, Lun; Huang, Neng; Yang, Li; Guo, Chuwen; Liu, Fang
Graphical abstract: Highlights: A new comprehensive method for recycling gas–solid wastes is proposed. The factors and mechanisms of influence on system efficiency are studied. The migration characteristics of heavy metal elements in wastes are characterized. Methane concentration lower than 1% could be efficiently converted. An advanced mechanical strength representation method is proposed. Abstract: Sewage sludge and red mud are industrial wastes that are potentially harmful to the environment. Their environmentally friendly treatment has been a global challenge due to their huge production and limited disposal capacity. Red mud, which contains Fe2 O3 and Al2 O3, can be used as an oxygen carrier. The organic matter contained in the sludge can be used as fuel. Based on the above characteristics, we propose a comprehensive waste reuse method: red mud was used as an oxygen carrier, sewage sludge was used as fuel and ultra-low concentration methane was used as an oxidizing gas. The method employs waste's heat and mass transfer properties to achieve comprehensive treatment and reuse of gas–solid phase waste. The factors influencing waste treatment efficiency as well as the mechanism of the reaction process have been thoroughly investigated. By adjusting the O/C ratio and water vapor percentage at 950℃, the carbon conversion and CO2 selectivity could reach 94.34 %, 76.50 %, respectively. The methane conversion was close to 99.80 %, and the H2 and CO yields were up to 37.98 × 10 −4  mol and 21.67 × 10 −4  mol, respectively. The microscopic morphology and properties of used OC particles remained stable. The migration characteristics of heavy metal elements indicated that bed material composed of sludge and red mud has the potential to be used as a raw material for construction after sieving. This study proposes a new comprehensive method for reusing sewage sludge, red mud, and low-concentration methane that would be efficiently recycled in one process.